Tissue Expansion for Severe Foot and Ankle Deformities: A 16-Year Review. Issue 4 (November 2018) - Nickel, Kevin J.; Van Slyke, Aaron C.; Knox, Aaron D.; Wing, Kevin; Wells, Neil
Background: Tissue expansion in the lower extremity is controversial, with studies reporting complication rates as high as 83%. Few studies have looked at tissue expansion prior to orthopaedic correction of severe foot and ankle deformities, and those available are restricted to clubfoot in the pediatric population. Here, we report the largest case series on the use of tissue expanders for the reconstruction of severe foot and ankle deformity and the only report in adults. Methods: This is a retrospective chart review of the senior author's practice over a 16-year study period. All patients over 18 years of age who underwent tissue expansion prior to definitive orthopaedic correction of a severe foot and ankle deformity were included. Patient demographics, etiology of deformity, rate of expansion, and complications were recorded. Major complications were defined as those which required surgical intervention. Data were analyzed using descriptive statistics. Results: Nineteen cases were performed on 16 patients. Our overall complication rate was 31.6% (6/19), with major complications occurring in 21.1% (4/19) of cases, and minor complications occurring in 10.5% (2/19) of cases. Despite this, 94.7% (18/19) of cases went on to receive definitive orthopaedic correction after tissue expansion. No demographic parameters were associated with occurrence of complications. Conclusions: This represents the largest report on lower extremity tissue expansion for severe foot and ankle deformity correction. While we observed complications in 31.6% of patients, 94.7% of cases went on to receive definitive orthopaedic correction with successful primary closure.